LOCAL GOVERNANCE AND HUMAN RIGHTS IN UPHOLDING CIVIC FREEDOMS, EQUITY, AND JUSTICE AT THE LOCAL LEVEL (Lex localis - Journal of Local Self-Government, 2025)
This paper explores the role of local governance in upholding human rights, particularly in ensuring civic freedoms, equity, and justice at the local level. The research focuses on how local government structures contribute to protecting fundamental rights, addressing inequalities, and fostering justice through participatory processes and legal frameworks. Using a qualitative analysis approach, this study evaluates the effectiveness of local governance mechanisms in promoting human rights. Findings reveal that strong local governance systems are essential in delivering equitable and justice-driven outcomes, although challenges remain in resource constraints and political will. The paper concludes with recommendations for improving local governance to protect human rights.